Parametric Analysis of Magnetorheological Strut for Semiactive Suspension System Using Taguchi Method - Yerrawar, R. N.; Arakerimath, R. R. (Engineering, Technology & Applied Science Research, 2018)
Magnetorheological (MR) strut is among the leading advanced applications of semi-active suspension systems. The damping force of MR damper is controlled by varying the viscosity of MR fluid. In this work, the viscosity of MR damper varies by changing the current from 0.5A to 0.7A. The design of experiments is taken into account in concert with the product/process development as one completely advanced tool. The parameters used for ride comfort optimization are sprung mass, spring stiffness, tire pressure, current, and cylinder material with two levels of each. Taguchi orthogonal array method is used to select the best results by parameter optimization with a minimum number of test runs. In this paper, from Taguchi L16 array and S/N ratio analysis, it is observed that the cylinder material with Al and CS for damper cylinder is a key parameter for performance measure of semi-active suspension system. From regression analysis, a linear mathematical model is developed for Al and CS as cylinder materials. The interaction of cylinder materials with all four parameters is plotted. The methodology implemented for measurement of acceleration as a ride comfort is as per IS 2631-1997. The more economical model of magnetorheological damper will motivate Indian auto industry to broader applications.